2017
DOI: 10.1111/dpr.12314
|View full text |Cite
|
Sign up to set email alerts
|

Millennium Development Goals: Impact on national strategies and spending

Abstract: This study reviews the post‐2005 national development strategies of 50 countries from diverse income groups, geographical locations, human development tiers and official development assistance (ODA) levels to assess Millennium Development Goal (MDG) absorption into development planning. Reviewing Poverty Reduction Strategy Papers (PRSPs) and non‐PRSP national strategies, the majority of the development plans have either adopted the MDGs as planning tools or ‘localized’ them in a meaningful way, using diverse a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…The cases provide “useful variation” (Seawright & Gerring, 2008, p. 296) based on the distinctive approaches to human development as demonstrated by their national planning strategies. Our study expands on other studies that have compared national planning strategies (e.g., Chimhowu et al, 2019; Seyedsayamdost, 2018), contributing to the international scholarship on both national planning and human development.…”
Section: Methodssupporting
confidence: 52%
See 1 more Smart Citation
“…The cases provide “useful variation” (Seawright & Gerring, 2008, p. 296) based on the distinctive approaches to human development as demonstrated by their national planning strategies. Our study expands on other studies that have compared national planning strategies (e.g., Chimhowu et al, 2019; Seyedsayamdost, 2018), contributing to the international scholarship on both national planning and human development.…”
Section: Methodssupporting
confidence: 52%
“…Social opportunities that are important for private life and facilitate the participation of individuals in political and economic activities. Such opportunities have been challenged by mutually reinforcing changes such as globalization, liberalization processes, and financial crises (Peet & Hartwick, 2015; Seyedsayamdost, 2018). These processes have fostered the delocalization of companies and investments and have rendered the employability of workers more flexible, informal, and uncertain (particularly of women and unskilled workers), limiting their access to social benefits, training, collective bargaining, and jobs (Nattrass & Seekings, 2018; Pogge, 2004).…”
Section: Human Developmentmentioning
confidence: 99%
“…It is well-acknowledged that global goal setting can have a profound impact on national strategies for poverty and inequality reduction. During the first decade of the new millennium, by way of introducing Poverty Reduction Strategy Papers (PRSPs), national development strategies incorporated the Millennium Development Goals (MDGs) into development planning (Seyedsayamdost 2018). In some instances, even non-PRSP national strategies also responded to MDGs, though the adaptation strategies differ by country context.…”
Section: The Case For Using Mpi Measuresmentioning
confidence: 99%
“…3 Adoption of MDGs is also likely to have improved the targeting and flow of official development assistance (ODA), ensuring that aid emphasizes human development and/or is disproportionately allocated to countries that need to make the most progress on the MDGs (Addison, Niño-Zarazúa, & Tarp, 2015). Moreover, MDGs adoption has influenced national development plans, leading to the introduction of Poverty Reduction Strategy Papers (see Seyedsayamdost, 2017). Early assessments have shown that these are, on balance, important means for making progress on MDGs (see Booth, 2003) and recent econometric evidence found that the effect of ensuing policies has led to greater reductions in headcount poverty and infant mortality (Elkins, Feeny, & Prentice, 2017).…”
Section: Introductionmentioning
confidence: 99%